2020
DOI: 10.14198/jhse.2020.152.14
|View full text |Cite
|
Sign up to set email alerts
|

The analysis of the results of the Olympic free-style wrestling champions

Abstract: The successful and effective management of sports training is impossible without the justified forecasting. The retrospective analysis of the sport career of elite sportsmen allows to identify interconnections of the competitions -results on various stages of the sporting career. Analysis of papers showed, there are no researches which would analyse the highest-level sportsmen in wrestling -Olympic champions. Aim of the research -to analyse results of the Olympic champions in wrestling from 1996 to the present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 16 publications
(18 reference statements)
1
7
0
6
Order By: Relevance
“…Ігри Олімпіад, що проводяться один раз на чотири роки, є найбільш значущими і престижними змаганнями світу. Вся чотирирічна підготовка спортсменів вищого класу спрямована на отримання права участі в цих змаганнях (отримання ліцензії) і завоювання на них медалі (Абдуллаєв, & Ребар, 2018;Латышев, Поляничко, Юшина, Еретик, & Барабаш, 2020;Латышев, Шандригось, & Мозолюк, 2016;Платонов, 2015;Тропин, & Бойченко, 2017;Latyshev, M., Latyshev, S., Korobeynikov, Kvasnytsya, Shandrygos, & Dutchak, 2020).…”
unclassified
See 1 more Smart Citation
“…Ігри Олімпіад, що проводяться один раз на чотири роки, є найбільш значущими і престижними змаганнями світу. Вся чотирирічна підготовка спортсменів вищого класу спрямована на отримання права участі в цих змаганнях (отримання ліцензії) і завоювання на них медалі (Абдуллаєв, & Ребар, 2018;Латышев, Поляничко, Юшина, Еретик, & Барабаш, 2020;Латышев, Шандригось, & Мозолюк, 2016;Платонов, 2015;Тропин, & Бойченко, 2017;Latyshev, M., Latyshev, S., Korobeynikov, Kvasnytsya, Shandrygos, & Dutchak, 2020).…”
unclassified
“…З 2001 року до 2013 року включно було 7 вагових категорій, з них 4 олімпійських (на Іграх 2004, 2008, 2012 р. ) 1 3 0 1 0 2009 5 2 3 0 2010 3 0 2 1 2011 6 3 2 1 2012 7 4 0 0 0 0 2013 6 1 1 1 2014 4 0 2 1 2015* 3 1 3 1 2016 7 0 0 0 0 0 2017 3 0 1 0 2018 1 0 3 1 2019 6 4 2 0 Латишев, Квасниця, Спесивих, & Квасниця, 2019), що є загальноприйнятим і відповідає природній періодизації спортивного тренування (Платонов, 2005 Latyshev, M., Latyshev, S., Korobeynikov, G. Kvasnytsya, O., Shandrygos, V., & Dutchak, Y. (2020).…”
unclassified
“…Considering the retrospective analysis, the significance of the junior success among the Olympic champions (Latyshev et al, 2020) is demonstrated: 41 wrestling careers of the Olympic gold medalists from 1996 to 2016has been analyzed. Twenty (48.8%) out of 41 Olympic wrestling gold medalists had started their international career before they turned 18 years (cadets age).…”
Section: Results Of Research and Discussionmentioning
confidence: 99%
“…In combat sports the victory is achieved as a result of a competition with other athlete, that is why the previous sporting success is one of the most objective parameter of the following success. The studies on identifying correlations between performance successes at various stages of preparation in combat sports such as judo (Julio et al, 2011;Barreiros, Côté, & Fonseca, 2012), taekwondo (Sadowski, Gierczuk, Miller, Cieśliński, & Buszta, 2012;Li et al, 2018), Greco-Roman wrestling (Korobeynikov & Radchenko, 2009;Tropin, 2013;Biac, Hrvoje, & Sprem, 2014;Karninčić, Baić, & Sprem, 2017), free-style wrestling (Podlivaev, 2005;Latyshev et al, 2020) have been conducted. The weight classes in combat sports are of a significant importance, although we have not found the studies which would show the dependence of the results at the junior and cadet levels on the results at the senior level in relation to the weight classes.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…минулого століття у працях зі спортивної боротьби, фехтування та боксу [2]. Попри широке представлення проблем тактики й тактичної підготовки у науково-методичній літературі, більшість сучасних досліджень зі спортивних єдиноборств мають методичне спрямування та не містять її обґрунтування як цілісної системи [3][4][5][6][7]. Однією з причин цього є те, що для усвідомлення суті тактики, стратегії та дотичних до них дефініцій у спорті загалом та у спортивних єдиноборствах зокрема використовують різні теорії: війни, конфлікту, предметно-перетворювальну, або теорію індивідуальної діяльності, інформації [1,2].…”
unclassified